Ag(i) induced H-type and Pd(ii) induced J-type phthalocyanines to enhance PDT applications: synthesis, optical behaviors, photochemical/photophysical properties, and DFT studies - Alagoz, Tenzile; Genc Bilgicli, Hayriye; Polat, Elif; Piskin, Hasan; Tuzun, Burak; Gunsel, Armagan; Erdogmus, Ali; Yarasir, M. Nilufer; Bilgicli, Ahmet T. (ROYAL SOC CHEMISTRY, 2025)
The literature shows that thiol compounds are important in various diseases, such as oxidative stress, enzymatic reactions, the respiratory system, metabolic disorders, and cancer. Thus, it is important to prepare derivatives of phthalocyanines, which have an important place in macrocyclic chemistry, substituted with biologically active thiol groups. Within the scope of this study, novel phthalonitrile derivative 3-(4-bromobenzylthio)phthalonitrile (1) and its metallophthalocyanine derivatives [ZnPc (2), CuPc (3), and CoPc (4)] were synthesized. The synthesized compounds were characterized by the combination of standard spectroscopic methods. The molecular structure of the synthesized phthalonitrile derivative and its related crystallographic features were determined by the single-crystal X-ray data analysis. The substitution with the thiol group of phthalocyanine molecules gives them high solubility features in organic solvents. Thus, the effect of self-aggregation behaviors on electronic spectra was determined in organic solvent media. Also, optical sensor properties in the presence of valuable metal ions were investigated by UV-Vis and fluorescence spectroscopy. Furthermore, the photochemical and photophysical properties of newly synthesized phthalocyanines were studied. Finally, the effect of Ag+ and Pd2+ ions on the singlet oxygen quantum yield was performed. According to the results, the newly synthesized ZnPc (2) is a good candidate for PDT as a photosensitizer. Also, the singlet oxygen quantum yield is highly improved in the presence of valuable metal ions such as Ag+ and Pd2+ ions.
Keywords: PHOTOCHEMICAL PROPERTIES; STRUCTURE VALIDATION; CONJUGATED POLYMERS; GOLD NANOPARTICLES; SUBSTITUENTS; AGGREGATION; IONS; Chemistry